THE SUBJECT SEXUALITY WORKED IN WORKSHOPS IN A PUBLIC SCHOOL OF PARANÁ (Fiep Bulletin - online, 2014)
The article reports the experience experienced by academics of nursing course to treat the subject sexuality with adolescents in the school environment. In adolescence the student faces several bodily and emotional changes and part of them are related to sexuality. Given this it is vital that the teachers along with their parents to extend their vision and work the theme of way lighter and unprejudiced, acting together with health professionals, aiming at an improvement in the quality of life and decrease in indicators of teenage pregnancy and sexually transmitted diseases. happened in two phases. The themes were worked in two phases, the first one was held in the presence of the teacher, where the theoretical content was verbally and with multimedia aid exposed, and also cured the doubts of the students. The second time we used a game called one remains, which is characterized by picking up one piece and make it jump over another piece, always horizontally or vertically, ending in an empty space. The piece that was skipped is removed from the Board. The game ends when you can no longer make any other move, at the end of practice the group who got more parts was the Group winner. Educational practices were identified that teenagers have a lot of curiosity and willingness to learn about sexuality in all its scope and when worked in form of workshops introducing games learning becomes more dynamic and fun. Sexual practices among teenagers and curiosity of age in relation to sex, requires the teacher preparation to work this complex theme with teenagers. Unfortunately, the textbooks offered to present the contents of human reproduction, limited to describe the anatomy and physiology of male and female reproductive systems and the playback mechanism.
Keywords: Sexuality; health education; nursing